Correlation of cryogenic deformation mechanisms to excellent strength-ductility of CrCoNi medium entropy alloy processed by selective laser melting - Kyung-Hwan Jung; Minh Tien Tran; Zhengtong Shan; Ho Won Lee; Sun-Kwang Hwang; Hyung Giun Kim; Dong-Kyu Kim (Journal of Materials Research and Technology, 2023)
The present study investigated the cryogenic mechanical properties and microstructure of CrCoNi medium entropy alloy (MEA) fabricated by selective laser melting (SLM) with hot isostatic pressing (HIP). The SLM processing parameters were optimized with respect to the relative density and micro-hardness of as-built CrCoNi specimens. The cryogenic (150 K) deformation mechanisms (compared to room (298 K) temperature) of SLM CrCoNi MEA were characterized by uniaxial tensile test, electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). At 150 K, it reveals superior mechanical properties with the noticeable increase in both strength and ductility by 6.5% and 10.0% (as-built), 22.7% and 6.6% (HIP-treated), respectively. It is found that the high cooling rate of 3.2 × 106 K/s obtained from the simulation results in the fine microstructure and high dislocation density, accordingly the high yield strength of SLM CrCoNi MEA. The steady work hardening, which postpones the onset of necking instability, is attributed to the pronounced dislocation activity and deformation twinning. In addition, a new phase with hexagonal closed-packed (HCP) substructure is apparently observed. Thus, a synergistic effect of dislocations, deformation twinning and HCP substructures contributes to the simultaneous enhancement of strength and ductility. These findings reveal that the CrCoNi MEA fabricated by SLM exhibits an excellent strength and ductility at cryogenic temperature. Furthermore, the SLM CrCoNi MEA with HIP shows significant improvement in the ductility with exceptional strength at 150 K. It demonstrates that a combination of SLM and HIP promotes the CrCoNi MEA to be promising for the cryogenic applications.